Studi Fenomenologi: Gambaran Pola Asuh Orang Tua Suku Lamaholot - Agusriani, Ade (NANAEKE: Indonesian Journal of Early Childhood Education, 2022)
Parenting pattern provided by each family differs from one another, both in perspective and in implementation. Parenting in Indonesia is generally carried out by mothers and fathers, however, in some families, it is not uncommon for grandmothers, grandfathers, and aunts to be involved. Differences in the involvement of various parties will have a separate impact on the growth and development of children. This research will provide an overview of the upbringing of the Lamaholot tribal family located in Pantai Harapan Village. This study uses qualitative methods with a phenomenological approach. Qualitative research data analysis was carried out from the time of data collection and was carried out carefully while in the field and afterward collecting data, assessing data quality, analyzing data, interpreting data, and making conclusions on the findings. The results of the study show that in general parents have implemented democratic parenting, where it is seen that parents apply parenting patterns by giving freedom to children but are still in control, there is two-way communication built by parents during parenting, and taking into account children’s wishes, as well as the existence of regulations that made at home to discipline children.